Improvement Strategy for Vita Nas Pineapple Juice Based on Consumer’s Importance and Performance Level - Mela, Ervina; Sadewa, Devanka Argabrahma; Wijayanti, Nur; Wijonarko, Gunawan (Indonesian Journal of Food Technology; Vol 5 No 1 (2026): Indonesian Journal of Food TechnologyDO - 10.20884/1.ijft.2026.5.1.18052, 2026)
Background: Fan's Food is a production house that processes the product Vita Nas pineapple juice drink. Entrepreneurs feel that businesses that should be growing tend to stagnate. Purpose: This study aims to determine the attributes that need to be improved based on the level of satisfaction, importance, and suitability of consumers, and formulate an improvement strategy. Method: Data was collected by questionnaire involving 100 respondents selected through purposive sampling. Result : The results showed that Vita Nas pineapple juice drink needs to be improved on the attributes of product availability, sales and promotion through online media, sweet taste of fruit juice, and packaging label design. The proposed strategies include expanding the distribution network through cooperation with agents, participating in digital marketing training, developing more attractive promotional content, product innovation by presenting low-sugar variants and updating packaging design involving professional graphic designers. The combination of these strategies is expected to increase Vita Nas' market share and strengthen its position in the beverage industry .